Power flow and transmission loss analysis of modular multi-level converter based multi-terminal high-voltage DC systems - Zhang, Yuanze; Ravishankar, Jayashri; Fletcher, John (IET renewable power generation, 2016)
Interconnected voltage-source converter based multi-terminal high-voltage DC (HVDC) systems provide better system redundancy, higher flexibility and capability of exchanging power between multiple areas. Recent developments in modular multi-level converter technology makes multi-terminal HVDC (MTDC) transmission more promising than before. This study provides an in-depth analysis of the power flow and transmission loss for MTDC systems with different grid topologies. A voltage–power droop control based algorithm is applied to solve the power flow problems. The main contribution of this study is the novel way of determining and calculating the transmission line losses for different MTDC network topology configurations. Three MTDC system topologies are investigated. Simulated case studies are used to observe the system power flow and transmission losses for all three topologies.